Non‐destructive observation of ferroelectric domain inverted structures in MgO:LiNbO3 by scanning electron microscope. Issue 12 (1st June 2015) - Tanaka, K.; Suhara, T.
Abstract : The non‐destructive observation of ferroelectric domain inverted (DI) structures in magnesium oxide (MgO)‐doped lithium niobate (LiNbO3 ) crystals by a scanning electron microscope is reported. The secondary electron emission coefficient dependent on the acceleration voltage is measured to find the second cross‐over voltage. The surface potential contrast formed by the pyroelectric charge was observed. The high‐contrast images of DI structures of 15 μm period for quasi‐phase matching is obtained in the telecom wavelength band.